Identification of the composition and abundance of microplastics in the digestive tract of fish in the Banjaran River, Banyumas District - Fadlali, Rizki; Rahayu, Nur Laila; Zaenuri, Musyarif (Acta Aquatica: Aquatic Sciences Journal, 2025)
Microplastics in the digestive tracts of fish can make their way into the food chain, reaching higher trophic levels, including humans, and potentially causing health issues. The Banjaran River in Banyumas Regency is one such waterway at risk of microplastic pollution. This study aimed to identify the types and abundance of microplastics in fish from the Banjaran River. Sampling was conducted at four strategically chosen stations based on land use, with three repetitions at two-week intervals. Analysis of the type composition and abundance of microplastics in the fish digestive tract using laboratory testing with microscope observations. Four types of microplastics were found in all samples with a predominance of fiber (37%), fragments (31%), pellets (19%), and film (14%). The abundance of microplastics in the fish digestive tract ranges from 12.8-20.5 particles/individual. The highest abundance of microplastics was found in broomstick fish, while the lowest abundance of microplastics was found in broomstick fish.Keywords: Banjaran River; Fish Digestion; Microplastics